Development of a Generic On-Line Departmental E-Library using the Iterative Design Approach - Olabisi, P. O.; Ogunkanmi, O. A.; Abdullahi, H. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
This work was based on the development of a departmental digital library that is generic in nature as can be adopted by departments of any specialisation. It aimed at providing easy access to textbooks, lecture materials, past questions, project reports, research theses, published articles, current innovations in the field of study of the department, and various online resources to facilitate academic excellence, efficient delivery of information and advance research activities. A generic iterative and incremental software design approach deployed and a well-structured database directory for managing e-resources was designed. The implementation took the two dimensions of the front-end client-side which involved designing both the user interface and user experience while considering factors such as accessibility, readability and usability and the back-end server-side operations which involved creating a connection between the front-end and the server and managing the database. HTML, CSS and Java Script were employed in programming the front-end while the back-end server side was programmed with PHP, MySQL, and a Content Management System. With e-resources uploaded into the cloud and results of tests conducted on the website showed average time to complete an e-resource search and download is 16.2 seconds, result of the readability test is 8.2 and the result of the accessibility test is 79 aggregated from the results of four different accessibility testers. The generic departmental e-library was developed with website designed to provide easy of online accessibility to students and staff of the department.